Practicality of Using E-Learning Learning Media in Entrepreneurship Courses - Maulana, Ilham Tri; Ganefri, Ganefri; Yulastri, Asmar (Journal International of Lingua and Technology, 2024)
This development research aims to develop a learning media in the form of E-Learning in entrepreneurship courses. This e-Learning is designed to improve student learning outcomes so that students can fully understand the material provided in the entrepreneurship course. This research uses the IDI (Instructional Development Institute) development method, the IDI development procedures are: define, develop, and evaluate. The type of data is primary data where data is provided by media experts, lecturers and students. The data analysis technique used is descriptive data analysis technique, namely by describing the validity and practicality of using E-Learning. The results obtained from this research and development are as follows; (1) The validity of E-Learning is declared very valid in the content and interest aspects with a total validity value of 84.54%, while in the media and language aspects it is declared valid with a total value of 85.55% (2) The practicality of E-Learning is based on lecturer responses after going through validation declared practical with a total score of 81.25%, while the practicality of E-learning based on student responses after going through validation was declared very practical with a total score of 82.75%. Based on the findings of this research, it was concluded that E-Learning is valid and practical to be used as a learning medium in entrepreneurship courses and recommended for other courses.